DEVELOPING INTERACTIVE LEARNING MEDIA FOR 8TH GRADE STUDENTS OF JUNIOR HIGH SCHOOL - Iin Baroroh Maarif (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2021)
ABSTRACT The objective of this research is developing Interactive Learning Media for 8th Grade Students of Junior High School. This is kind of learning media needed by the students in this era which consist of some materials which is appropriate for students. All materials are based on junior high school syllabus of curriculum K13. This research used Research and Development method. This development used ADDIE model that have five steps, those are; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The results of this research (from the results of validation stage to the results of implementation stage) showed that This learning media is feasible to be used as a learning media for 8th grade students of junior high school. By having those conclusion, it means that this research can be used as reference to other researcher in developing English learning media in different level of students. Key words: Interactive learning media, English skill, Junior High School Students ABSTRAK Penelitian ini bertujuan untuk mengembangkan Media Pembelajaran Interaktif Siswa Kelas VIII SMP. Media pembelajaran seperti inilah yang dibutuhkan oleh siswa di era sekarang ini yang terdiri dari beberapa materi yang sesuai untuk siswa. Semua materi berdasarkan silabus SMP kurikulum K13. Penelitian ini menggunakan metode Research and Development. Pengembangan ini menggunakan model ADDIE yang memiliki lima langkah, yaitu; 1) Analisis, 2) Desain, 3) Pengembangan, 4) Implementasi, dan 5) Evaluasi. Hasil penelitian ini (dari hasil tahap validasi hingga hasil tahap implementasi) menunjukkan bahwa media pembelajaran ini layak digunakan sebagai media pembelajaran siswa kelas VIII SMP. Dengan adanya kesimpulan tersebut, berarti penelitian ini dapat digunakan sebagai referensi bagi peneliti lain dalam mengembangkan media pembelajaran bahasa Inggris pada tingkat siswa yang berbeda. Kata kunci: Media Pembelajaran Interaktif, Keterampilan Bahasa Inggris, Siswa SMP